2010
DOI: 10.1038/labinvest.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB3 modulates TGF-β expression in chronic liver disease

Abstract: Transforming growth factor-b1 (TGF-b1) is the master cytokine in the pathogenesis of liver fibrosis. TGF-b1 and extent of fibrosis were correlated recently to the serpin SERPINB3 in idiopathic pulmonary fibrosis, a chronic disease recalling liver cirrhosis. The aim of this study was to assess the relation between SERPINB3, TGF-b1 and fibrosis in chronic liver diseases and to determine the effect of this serpin on TGF-b1 expression using in vitro models. SERPINB3 and TGF-b1 were evaluated in liver biopsies of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 41 publications
(45 reference statements)
2
68
0
Order By: Relevance
“…Recent results indicate that SERPINB3 can induce RSL-dependent TGF-b1 synthesis and the effect is modulated by single amino acid mutation in the reactive loop. 20 In chronically damaged livers, a parallel over-expression of SERPINB3 and TGF-b1 was correlated directly to the fibrosis stage, as Figure 4 Inhibition of papain by SERPINB3 isoforms. The interaction of papain with SERPINB3 wild-type and SCCA-PD was studied under pseudo-first-order conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Recent results indicate that SERPINB3 can induce RSL-dependent TGF-b1 synthesis and the effect is modulated by single amino acid mutation in the reactive loop. 20 In chronically damaged livers, a parallel over-expression of SERPINB3 and TGF-b1 was correlated directly to the fibrosis stage, as Figure 4 Inhibition of papain by SERPINB3 isoforms. The interaction of papain with SERPINB3 wild-type and SCCA-PD was studied under pseudo-first-order conditions.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that in patients with chronic hepatitis undergoing standard antiviral treatment and achieving a sustained virological response there was a significant decrease in serum levels of SCCA-IgM at the end of treatment and up to 1 year of follow-up [21]. We might speculate that the damage inferred by a metabolic imbalance could be different from that caused by viral chronic infection, in which the use of SCCA-IgM has been validated [14, 16, 19-22]. Indeed, it is well known that adipose tissue is characterized by a state of low-grade inflammation that is the basis of the pathogenesis of NAFLD [38].…”
Section: Discussionmentioning
confidence: 99%
“…The two isoforms SCCA1 (SERPINB3) and SCCA2 (SERPINB4) are physiologically expressed in squamous epithelia, in endothelial cells of the veins, in the walls of arteries [14], and in peripheral blood mononuclear cells [15]. It has been reported that SERPINB3 induces TGFβ expression in chronic liver disease [16] and promotes fibrogenesis in experimental models [17]. Data indicate that SERPINB3 protects cellular from apoptotic death caused by different kinds of stimuli [18], inducing cell proliferation and increasing invasiveness potential.…”
Section: Introductionmentioning
confidence: 99%
“…These important clinical findings were confirmed at the mole cular level: SCCA expression in liver tumor has been correlated with liver regeneration activity (expressed by MIB-I-labeling index) [39] , and increased proliferation was also documented in hepatoma cell lines overexpressing SERPINB3 and in a mouse model transgenic for this serpin [39,40] . Recent data indicate that SERPINB3 is highly expressed in the hepatic stem/progenitor cell compartment of both fetal and adult livers [41] ; moreover, after induction by HIF2-alpha in an hypoxic environment [42] , SERPINB3 was shown to be crucial for tumour invasiveness and metastasis, since it promotes epithelial-mesenchymal transition [39] and transforming growth factor-beta production [43] (Figure 1). …”
Section: Sccamentioning
confidence: 99%